Comparative Study of Sperm DNA Isolation Method for Forensic Analysis - Patricia Gita Naully (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2020)
Forensic is a multi-discipline science that is used to obtain evidence of various criminal cases, such as rape. DNA analysis on sperm specimen is needed to identify the rapist. However, the success of this analysis depends on the DNA isolation method used. Several methods of DNA isolation from human sperm have been developed, but no method has been proven effective for the forensic analysis need. This study aimed to determine the effective sperm DNA isolation method for forensic analysis. In this study, the DNA of sperm specimens was isolated using three methods: Boiling Water, modified TRIzol, and Chelex-100. The DNA isolation result was visualized using agarose gel electrophoresis method. The concentration and purity of isolated DNA were measured using a Nanodrop by comparing the absorbance of DNA at λ 260 nm and protein at λ 280 nm. The effectiveness of the sperm DNA isolation method was determined based on the concentration and purity of DNA, the specimen volume, the implementation time, and the costs involved. The result showed that the successful methods for isolating sperm DNA were TRIzol and Chelex-100. The quantity of DNA isolated using the modified TRIzol method was 1,5 times higher than Chelex-100 but equired 120 times more specimen volume than Chelex-100. From 25 µl sperm specimens, the concentration of DNA isolated using the Chelex-100 method was 612.6 ng/µl with a purity of about 1.7. Therefore, it can be concluded that the Chelex-100 is the most effective method for isolating sperm DNA for forensic analysis.